The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1021/bi00371a019
|View full text |Cite
|
Sign up to set email alerts
|

The dnaB protein of Escherichia coli: mechanism of nucleotide binding, hydrolysis, and modulation by dnaC protein

Abstract: The mechanism of nucleotide binding and hydrolysis by dnaB protein and dnaB X dnaC protein complex has been studied by using fluorescent nucleotide analogues. Binding of trinitrophenyladenosine triphosphate (TNP-ATP) or the corresponding diphosphate (TNP-ADP) results in a blue shift of the emission maximum and a severalfold amplification of the fluorescence emission of the nucleotide analogues. Scatchard analysis of TNP-ATP binding indicates that TNP-ATP binds with a high affinity (Kd = 0.87 microM) and a 8.5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
48
2

Year Published

1996
1996
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(51 citation statements)
references
References 31 publications
1
48
2
Order By: Relevance
“…Alternatively, 3D EM reconstructions of an Ec DnaB•DnaC complex have shown that upon binding of DnaC, contacts between the globular domains of the DnaB N-terminal collar rearrange into a cracked , but constricted, configuration (Arias-Palomo et al, 2013). Given that DnaC is present in our unwinding assays, and that the loader is known to prevent DnaB from unwinding DNA when it stays associated with the helicase (Biswas et al, 1986; Wahle et al, 1989), the observed differences in rate between wild-type and mutant DnaBs seen here could derive from a change in the relative affinity of DnaC for the helicase depending on the state of the collar. In this view, a constricted collar state would favor DnaC binding, slowing release of the loader from the helicase and leading to a long lag that precedes unwinding.…”
Section: Resultsmentioning
confidence: 81%
“…Alternatively, 3D EM reconstructions of an Ec DnaB•DnaC complex have shown that upon binding of DnaC, contacts between the globular domains of the DnaB N-terminal collar rearrange into a cracked , but constricted, configuration (Arias-Palomo et al, 2013). Given that DnaC is present in our unwinding assays, and that the loader is known to prevent DnaB from unwinding DNA when it stays associated with the helicase (Biswas et al, 1986; Wahle et al, 1989), the observed differences in rate between wild-type and mutant DnaBs seen here could derive from a change in the relative affinity of DnaC for the helicase depending on the state of the collar. In this view, a constricted collar state would favor DnaC binding, slowing release of the loader from the helicase and leading to a long lag that precedes unwinding.…”
Section: Resultsmentioning
confidence: 81%
“…San Martin et al (30) has shown that the DnaB oligomer is a trimer of asymmetrical dimers with a pronounced triangular shape. In addition, DnaB exhibits three high affinity binding sites for ATP analogs, which further supports the 3-fold symmetry of this hexameric molecule (48,50). In the case of the DnaC-DnaB hexamer complex, each DnaB monomer provides a binding site for a DnaC and thus exhibits a 6:1 stoichiometric ratio (56).…”
Section: Stoichiometry Of the Complex [Primase-dnab Hexamer] Ismentioning
confidence: 70%
“…This replication factor is required for assisting DnaB to bind to the replication origin and appears to have a pivotal role in initiation of helicase function (50,51). Previous studies demonstrated that in vitro DnaC forms a tight complex with the DnaB helicase in the complete absence of nucleotides and DNA (52).…”
Section: Analysis Of In Vitro Primer Synthesis In the Presence Of Dnamentioning
confidence: 99%
“…It is likely that this structural dimerization correlates with the biochemical non-equivalence of subunits observed for other hexameric helicases. The T7 gp4 hexamer, for example, has been shown to contain only three, not six, high affinity ATP-binding sites (52), as has the hexameric rho protein (53) and DnaB (54).…”
Section: Discussionmentioning
confidence: 99%